Spatial distribution and driving force analysis of soil heavy metals in the water source area of the middle route of the South-to-North Water Diversion Project - Yi Wu; Changyan Zhou; Wenyou Hu; Mingyang Li; Li Ding (Ecological Indicators, 2024)
The South-to-North Water Diversion Project is crucial for ensuring water security in Beijing and balancing water resource distribution between China's northern and southern regions. The quality and distribution of soil heavy metals in the water source area significantly affect the project's water quality. However, many previous studies lack the analysis of the whole water source area for the middle route of the South-to-North Water Diversion Project. In this study, 116 soil quadrats data obtained during the baseline survey in September 2015, combined with data including the Digital Elevation Model (DEM), Fractional Vegetation Cover (FVC), population density, Gross Domestic Product (GDP), were collected and the Single Factor Pollution Index (SFPI) method, the Nemerow Comprehensive Pollution Index (NCPI) method and the Geographical Detector (Geodetector) model were used to study the pollution conditions and spatial distribution of soil heavy metals in the study area. The research results show that: (1) the number of soil quadrats exceeding the standard for the heavy metal elements As, Cd, Cr, Cu, and Ni was 3, 3, 1, 1, and 1, respectively, indicating a low to moderate pollution level with an average NCPI value of 0.91; (2) the average soil contents of As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn in cropland quadrats were 11.71, 0.29, 78.66, 32.04, 0.09, 37.34, 27.41, and 97.52 mg·kg−1, respectively, while the average soil heavy metal contents in forest land were 9.03, 0.21, 64.26, 31.39, 0.05, 31.85, 25.7, and 88.62 mg·kg−1, respectively, indicating the forest soil quality was better than cropland; (3) higher concentrations of heavy metals (hot spots) were observed in the northern and southern parts of the study area, while the eastern part exhibited lower concentrations (cold spots); (4) the heavy metal content in the soil is closely related to the precipitation intensity (q = 0.35) and economic development level (q = 0.28) of the area. The study concludes that to safeguard the soil quality in the water source area, measures such as forest land conservation, reduction in chemical fertilizer and pesticide use, and industrial pollution control are imperative. By providing a detailed quantitative assessment of soil heavy metal pollution, this research offers valuable insights for policy formulation and environmental management strategies making to ensure the sustainability of the South-to-North Water Diversion Project.